2015
DOI: 10.1002/stem.2235
|View full text |Cite
|
Sign up to set email alerts
|

Ataxia Telangiectasia Mutated Dysregulation Results in Diabetic Retinopathy

Abstract: Ataxia telangiectasia mutated (ATM) acts as a defense against a variety of bone marrow (BM) stressors. We hypothesized that ATM loss in BM-hematopoietic stem cells (HSCs) would be detrimental to both HSC function and microvascular repair while sustained ATM would be beneficial in disease models of diabetes. Chronic diabetes represents a condition associated with HSC depletion and inadequate vascular repair. Gender mismatched chimeras of ATM−/− on wild type background were generated and a cohort were made diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
1
19
0
Order By: Relevance
“…Trypsin digestion of the retina was performed according to a previously published protocol [32,33]. Briefly, eyeballs were enucleated and incubated in 4% paraformaldehyde overnight.…”
Section: Acellular Capillaries Quantificationmentioning
confidence: 99%
“…Trypsin digestion of the retina was performed according to a previously published protocol [32,33]. Briefly, eyeballs were enucleated and incubated in 4% paraformaldehyde overnight.…”
Section: Acellular Capillaries Quantificationmentioning
confidence: 99%
“…We reported that ataxia telangiectasia mutated (ATM) is critical for maintaining long-term populating HSCs in the bone marrow [17]. ATM helps correct DNA damage by recruiting DNA repair proteins to sites of DNA damage.…”
Section: Bone Marrow and Hematopoietic Stem/progenitor Cells (Hs/pcs)mentioning
confidence: 99%
“…An imbalance in the sympathetic nervous system, with the loss of parasympathetic drive and increased sympathetic activation, occurs in diabetes. Ultimately these neuronal changes transition to neuronal loss and in the bone marrow can directly impact diabetic retinopathy [16, 17, 27, 28, 30, 37, 38, 47-50]. In chronic diabetes bone marrow denervation occurs and precedes the onset of diabetic retinopathy in rodent models of diabetes [28, 30, 37, 49].…”
Section: The Bone Marrow- Brain Connection In the Pathogenesis Of Diamentioning
confidence: 99%
“…A study of gene expression profiling of human CD34+ cells isolated from patients with diabetes, with and without microvascular complications, also showed upregulation of IL1β in the patient groups with diabetes compared to controls without diabetes . IL1β expression was increased further in cells isolated from patients with diabetes and complications.…”
Section: Discussionmentioning
confidence: 94%